An Analysis of Cooperative Learning Model Think Pair Share to Train Student’s Writing Skill - Nisa, Laivia Corilla; Mahsunah, Evi (Nusantara Educational Review, 2024)
This research describes the application of the think pair share cooperative learning model to train students' writing skills at MTs Sabilil Khoir Porong and student responses. This research only focuses on students' writing skills, especially descriptive text material in class nine, second semester. This research uses descriptive qualitative as a research design. Data was obtained by observation and questionnaires. The research results show that the use of think pair share can train students' writing skills in the descriptive text for ninth-grade students at MTs Sabilil Khoir Porong in the 2022/2023 academic year. The implementation of think pair share was successful because students became more active in discussing writing descriptive texts with their partners based on the think pair share steps. The results of the questionnaire show that students agree that the think pair share cooperative learning model is interesting and can help them practice writing descriptive texts. Penelitian ini bertujuan untuk mendeskripsikan penerapan model pembelajaran kooperatif think pair share untuk melatih keterampilan menulis siswa di MTs Sabilil Khoir Porong dan respon siswa. Penelitian ini hanya berfokus pada keterampilan menulis siswa khususnya materi teks deskriptif di kelas sembilan semester dua. Penelitian ini menggunakan deskriptif kualitatif sebagai desain penelitian. Data diperoleh dengan observasi dan kuesioner. Hasil penelitian menunjukkan bahwa penggunaan think pair share dapat melatih keterampilan menulis siswa pada teks deskriptif pada siswa kelas sembilan MTs Sabilil Khoir Porong tahun ajaran 2022/2023. Implementasi think pair share berhasil karena siswa menjadi lebih aktif dalam berdiskusi tentang menulis teks deskriptif dengan pasangannya berdasarkan langkah-langkah think pair share. Hasil lembar angket menunjukkan bahwa siswa setuju model pembelajaran kooperatif think pair share menarik dan dapat membantu mereka dalam melatih menulis teks deskriptif.